Accessibility Dilemma in Metro Stations: An Experimental Pilot Study Based on Passengers’ Emotional Experiences - Soto-Lagos, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
This study explores the passengers’ accessibility dilemma in Valparaíso, Chile, through field observations and laboratory experiments. The aim is to investigate the accessibility in metro stations based on the users’ emotional experience. Perceptions were reported through the emotions of passengers according to a circumplex psychological model and an accessibility ranking. Passengers reported their emotions (e.g., stress, sadness, relaxation, and happiness) during different trip moments. Results indicate that rearranging train seats parallel to movement creates a more spacious aisle, enhancing mobility and evoking positive emotions such as happiness. However, an unexpected rise in sadness suggests that social dynamics may influence emotional responses, warranting further investigation. Overcrowding increases stress and sadness, emphasizing the need for capacity management to improve passengers’ emotional experiences. Field observations reveal that early journey stages, such as walking to the station or waiting on the platform, are associated with unpleasant experiences due to poor infrastructure and accessibility barriers. In contrast, train rides foster more positive emotions, credited to better accessibility onboard. Passenger dissatisfaction arises from issues such as elevator malfunctions, inconsistent train schedules, and inadequate station accessibility. This study could help to understand passenger behavior when the accessibility conditions of metro stations and their surroundings are changed. Further studies will expand the concept of emotions by considering social and psychological factors and explore different types of stations and their surroundings considering a larger sample size in laboratory experiments and field studies. © 2025 by the authors.